Implementation of integrated IoT-based monitoring system to improve clean water services at KP-SPAMS Tirta Jatisari - Arga Dwi Pambudi; Zaenal Arifin; Nur Islahudin; M Ary Heryanto; Helmy Rahadian; Aries Jehan Tamami; Syahri Muharrom (Universitas Muhammadiyah Magelang, 2024)
The Tirta Jatisari Water Supply and Sanitation Management Group (KP-SPAMS) faced challenges ensuring transparency in water usage and efficiency in billing due to the limitations of conventional water meters. These meters lacked real-time monitoring capabilities, hindering leak detection and leading to billing inaccuracies. To address this, an Internet of Things (IoT)-based monitoring system integrated with a web application was implemented to improve transparency and operational efficiency. The methodology involved needs analysis and system design, IoT device development, installation of flow meter sensors, development of a user-friendly web application for both KP-SPAMS managers and consumers, and comprehensive system training and socialization. Results demonstrated improved billing accuracy and speed, along with real-time water usage monitoring for both KP-SPAMS and consumers, facilitating timely leak detection. The implementation successfully increased consumer satisfaction and fostered the development of technologically adept human resources.